Determinants of intention to give Zakat on employment income: experience from Marawi City, Philippines - Andam, Abdullah Campong; Osman@Hussin, Ahmad Zamri (2016)
Zakat is third of the five pillars of Islam. Its importance to the Muslims is highly valued in Islam. Various zakat studies have been undertaken including the legal, Islamic jurisprudence, management, business with different approaches and conceptual underpinnings. The majority of the studies, especially in the management literature focus on Islamic or/and Muslim-majority countries/jurisdictions. However, there is a dearth of discussion or/and empirical findings in the non-Muslim majority area. This study provides such opportunity as it explores zakat issues in Philippines – a Christian majority country. The findings provide new insights into a nonMuslim country setting where no zakat institutions operate. Although Muslims is a minority in the country, the number as a whole is considered significant, hence the need to understand the importance of zakat issues. The study aims at identifying the factors influencing intention to give zakat which focuses on the employment income. The study used the Extended Theory of Planned Behaviour – an extension of the Theory of Reasoned Action – to investigate the factors influencing intention to give zakat. The theory introduces six variables in predicting the intention to give zakat (i.e., attitude, perceived behavioural control, injunctive norm, descriptive norm, moral norm and past behaviour). Questionnaires were directly distributed to the respondents in a Muslimmajority area (i.e. Marawi City). The data have been analysed using multiple regression analysis. The findings show that attitude, descriptive norm and moral norm have a positive relationship with the intention to give zakat. Meanwhile, perceived behavioural control, injunctive norm and past behaviour are found to have insignificant influence over intention. Among the factors identified, attitude is found to be the strongest predictor of intention. In addition, the findings of the study disagree with prior studies who claim that descriptive norm is only found to be a predictor of intention on non-altruistic setting. But overall, the study supports the extension of the theory of planned behaviour which accounts for 53% of the variance in intention.